Understanding the physical basis for the side‐chain conformational preferences of methionine. Issue 7 (6th April 2016) - Virrueta, Alejandro; O'Hern, Corey S.; Regan, Lynne
ABSTRACT: Methionine (Met) is a structurally versatile amino acid most commonly found in protein cores and at protein–protein interfaces. Thus, a complete description of the structure of Met is important for a fundamental understanding of protein structure and design. In previous work, we showed that the hard‐sphere dipeptide model is able to recapitulate the side‐chain dihedral angle distributions observed in high‐resolution protein crystal structures for the nine amino acids we have studied to date: Val, Thr, Ser, Leu, Ile, Cys, Tyr, Trp, and Phe. Using the same approach, we are also able to predict the observed χ 1 and χ 2 side‐chain dihedral angle distributions for Met. However, the form of the side‐chain dihedral angle distribution P ( χ 3 ) predicted by the hard‐sphere model does not match the observed distribution. We investigate the possible origins of the discrepancy and find that specific bond lengths and angles in Met side chains strongly influence P ( χ 3 ). We then identify minimal additions to the hard‐sphere dipeptide model necessary to quantitatively predict P ( χ 3 ) of Met, and its near isosteres norleucine (Nle) and selenomethionine (Mse). We find that adding weak attractive interactions between hydrogen atoms to the model is sufficient to achieve predictions for P ( χ 3 ) that closely match the observed P ( χ 3 ) distributions for Met, Nle, and Mse. We explicitly show that weak attractive interactions between hydrogens do not negatively affect the agreement between the predicted and observed side‐chain dihedral angle distribution for Val, Leu, Ile, and Phe, as we expect for other amino acids. Proteins 2016; 84:900–911. © 2016 Wiley Periodicals, Inc.